Assessing the effects of an acute exposure to worst-case concentration of Cry proteins on zebrafish using the embryotoxicity test and proteomics analysis. (February 2021) - Vieira, Leonardo; Hissa, Denise Cavalcante; Souza, Terezinha; Gonçalves, Íris Flávia Sousa; Evaristo, Joseph Alberto Medeiros; Nogueira, Fábio César Sousa; Carvalho, Ana Fontenele Urano; Farias, Davi
Abstract: Cry1C, Cry1F and Cry1Ab are insecticidal proteins from Bacillus thuringiensis ( Bt ) which are expressed in transgenic crops. Given the entry of these proteins into aquatic environments, it is relevant to evaluate their impacts on aquatic organisms. In this work, we sought to evaluate the effects of Cry1C, Cry1F and Cry1Ab on zebrafish embryos and larvae of a predicted worst-case scenario concentration of these proteins (set to 1.1 mg/L). For that, we coupled a traditional toxicity approach (the zebrafish embryotoxicity test and dosage of enzymatic biomarkers) to gel free proteomics analysis. At the concentration tested, these proteins did not cause adverse effects in the zebrafish early life stages, either by verifying phenotypic endpoints of toxicity or alterations in representative enzymatic biomarkers (catalase, glutathione-S-tranferase and lactate-dehydrogenase). At the molecular level, the Cry proteins tested lead to very small changes in the proteome of zebrafish larvae. In a global way, these proteins upregulated the expression of vitellogenins. Besides that, Cry1C e Cry1F deregulated heterogeneous nuclear ribonucleoproteins (Hnrnpa0l and Hnrnpaba, respectively), implicated in mRNA processing and gene regulation. Overall, these data lead to the conclusion that Cry1C, Cry1F and Cry1Ab proteins, even at a very high concentration, have limited effects in the early stages of zebrafish life. Graphical abstract: Image 1 Highlights: Cry1C, Cry1F and Cry1Ab proteins did not induce malformations or mortality in zebrafish embryos/larvae. Cry proteins did not cause changes in enzyme biomarkers of zebrafish larvae. Cry proteins induced minor disturbances in the proteome of zebrafish larvae. Cry1C, Cry1F and Cry1Ab proteins have no deleterious effects on fish.